Association Studies in Populus tomentosa Reveal the Genetic Interactions of Pto-MIR156c and Its Targets in Wood Formation - Quan, Mingyang; Wang, Qingshi; Phangthavong, Souksamone; Yang, Xiaohui; Song, Yuepeng; Du, Qingzhang; Zhang, Deqiang (Frontiers in Plant Science, 2016)
MicroRNAs (miRNAs) regulate gene expression in many biological processes, but the significance of the interaction between a miRNA and its targets in perennial trees remains largely unknown. Here, we employed transcript profiling and association studies in Populus tomentosa (Pto) to decipher the effect of genetic variation and interactions between Pto-miR156c and its potential targets (Pto-SPL15, Pto-SPL20, and Pto-SPL25) in 435 unrelated individuals from a natural population of P. tomentosa. Single-SNP (single-nucleotide polymorphism) based association studies with analysis of the underlying additive and dominant effects identified 69 significant associations (P < 0.01), representing 51 common SNPs (minor allele frequency > 0.05) from Pto-MIR156c and its three potential targets, with six wood and growth traits, revealing their common roles in wood formation. Epistasis analysis uncovered 129 significant SNP-SNP associations with ten traits, indicating the potential genetic interactions of Pto-MIR156c and its three putative targets. Interestingly, expression analysis in stem (phloem, cambium, and xylem) revealed that Pto-miR156c expression showed strong negative correlations with Pto-SPL20 (r = -0.90, P < 0.01) and Pto-SPL25 (r = -0.65, P < 0.01), and a positive correlation with Pto-SPL15 (r = 0.40, P < 0.01), which also indicated the putative interactions of Pto-miR156c and its potential targets and their common roles in wood formation. Thus, our study provided an alternative approach to decipher the interaction between miRNAs and their targets and to dissect the genetic architecture of complex traits in trees.